Evidence for Reciprocal Structural Network Interactions Between Bilateral Crus Lobes and Broca’s Complex - Zhang, Hui; Bao, Yue; Feng, Yuan; Hu, Haijun; Wang, Yibao (Frontiers in Neuroanatomy, 2020)
While the proximal dentatothalamocortical tracts are considered pivotal in the occurrence of cerebellar mutism syndrome (CMS) after medulloblastoma resection, how the cerebellum participates in motor-speech networks through direct structural connectivity is still unclear. Via tractography, we provide evidence of cerebellar streamlines projecting into the left inferior frontal gyrus majorly connected Broca’s complex and the bilateral Crus lobes. The streamlines, named as Crus-Broca tracts, originated from the bilateral Crus lobes, synapsed onto the dentate nucleus (DN), ascended into the superior cerebellar peduncle (where these streamlines were closely superior to the superior border of the supratonsillar cleft and the superolateral roof of the fourth ventricle), surprisingly bypassed the left red nucleus and the left thalamus, and ended at subregions of Broca’s complex. The streamlines, named as Broca-Crus tracts, originated from subregions of Broca’s complex and ended predominantly at the right Crus lobes. If verified, existence of these connections would support the notion of the bilateral cerebellums‘ participating in motor speech planning and the anatomical relationship of Broca-Crus tracts with the supratonsillar cleft would merit consideration for further studies aimed at further elucidating CMS mechanisms.